Kurangnya Unsur Hara pada Tanaman Cabai Merah serta Pemeliharaannya - Nice Anjelin Gulo; Ayu Indah Purnama Mendrofa; Berliana Vivi Lestari Lase; Cynthia Florentina Mendrofa; Iman Viktor Telaumbanua; Irwan Saham Laia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research examines the causes of the lack of nutrients in red chili plants (Capsicum annuum L.) and how to properly maintain them. Using qualitative descriptive research methods, this study was conducted in Dahadano Botombawo Village, Hiliserangkai District, Nias Regency for 3 months. Research results show that deficiencies in key nutrients such as nitrogen, phosphorus, potassium, calcium and magnesium can cause various symptoms in chili plants, including stunted growth and reduced fruit quality. Factors such as environmental conditions, soil quality, pest and disease attacks, and inappropriate cultivation practices also contribute to delayed plant growth. Proper maintenance, including selecting quality seeds, good soil cultivation, appropriate fertilization, and integrated pest and disease control, is very important to increase the productivity of red chili plants.